2020
DOI: 10.1051/0004-6361/202038080
|View full text |Cite
|
Sign up to set email alerts
|

Role of the impact parameter in exoplanet transmission spectroscopy

Abstract: Context. Transmission spectroscopy is a promising tool for the atmospheric characterization of transiting exoplanets. Because the planetary signal is faint, discrepancies have been reported regarding individual targets. Aims. We investigate the dependence of the estimated transmission spectrum on deviations of the orbital parameters of the star-planet system that are due to the limb-darkening effects of the host star. We describe how the uncertainty on the orbital parameters translates into an uncertainty on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…It, hence, enters calculations of transmission depth being expressed in terms of pressure scale heights (H = k B T eq /(µg P ); e.g. Alexoudi et al 2020) or for deriving a cloud top pressure for defining an isothermal transit radius (Heng 2019). A constant value of µ is often assumed when running a 3D GCM (see introduction in Drummond et al 2018) as it is beneficial computationally.…”
Section: Mean Molecular Weightmentioning
confidence: 99%
“…It, hence, enters calculations of transmission depth being expressed in terms of pressure scale heights (H = k B T eq /(µg P ); e.g. Alexoudi et al 2020) or for deriving a cloud top pressure for defining an isothermal transit radius (Heng 2019). A constant value of µ is often assumed when running a 3D GCM (see introduction in Drummond et al 2018) as it is beneficial computationally.…”
Section: Mean Molecular Weightmentioning
confidence: 99%
“…Better constrained b values, derived from a well acquired information on ingress and egress, place the planet to a more precise orbital configuration around its host. This consequently can yield a more robust R p value, since the planetary radii are usually vulnerable towards the stellar limb darkening modeling process (Alexoudi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The derived value of the radius of an exoplanet is strongly affected by the orbital set-up of the system. If the planet is transiting its host star centrally ( b=0) or over the limbs ( b=1), this plays a major role in the correct estimation of the transit depth (Alexoudi et al 2020). As we saw previously, b depends on i and a/R s .…”
Section: The Relations Between the Planetary Radii And The Impact Par...mentioning
confidence: 99%
“…A.1), which should not be responsible for biases in a large wavelength range. Alexoudi et al (2018) and Alexoudi et al (2020) suggest that a fixed but inaccurate orbital inclination or impact parameter will cause a different slope and a systematic offset in the optical transmission spectrum. As illustrated in Fig.…”
Section: Rmse=381 Ppmmentioning
confidence: 99%
“…In contrast to the space-based observations, the ground-based observations reported by Mallonn et al (2015) and Yan et al (2020) presented relatively flat and featureless transmission spectra in the optical, favoring a cloudy atmosphere. Alexoudi et al (2018Alexoudi et al ( , 2020 proposed that such discrepancy in the offsets and slopes of transmission spectra can be attributed to the inaccuracy of orbital geometry parameters (semi-major axis, orbital inclination, or impact parameters) used in the spectroscopic light curve fitting. In addition, Deibert et al (2019) performed high-resolution transit spectroscopy on HAT-P-12b, and they revealed a 3.2σ detection of sodium absorption for the first time.…”
Section: Introductionmentioning
confidence: 99%